2018
DOI: 10.9745/ghsp-d-18-00105
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mid-Upper Arm Circumference by Novel Community Platforms to Detect, Diagnose, and Treat Severe Acute Malnutrition in Children: A Systematic Review

Abstract: Limited studies suggest that with robust program inputs caregivers and CHWs can correctly use mid-upper arm circumference to detect severe acute malnutrition (SAM) and that properly trained and supported CHWs can treat uncomplicated SAM in communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 27 publications
2
42
1
1
Order By: Relevance
“…The MUAC measurement was used over weight-for height below − 3 SD of the WHO standards because both of these measures give almost similar prevalence of SAM [3]. MUAC is regarded as a costeffective and easiest method to early detect SAM in children with minimal risk and many potential benefits [34]. We found that only 5.8% of children admitted to the OCCTs were severely malnourished.…”
Section: Discussionmentioning
confidence: 99%
“…The MUAC measurement was used over weight-for height below − 3 SD of the WHO standards because both of these measures give almost similar prevalence of SAM [3]. MUAC is regarded as a costeffective and easiest method to early detect SAM in children with minimal risk and many potential benefits [34]. We found that only 5.8% of children admitted to the OCCTs were severely malnourished.…”
Section: Discussionmentioning
confidence: 99%
“…MUAC is clearly an easier and quicker screening tool at community level than weight-for-height. Mothers and health volunteers have shown their capacity of detecting SAM [5] in several countries of Africa with good sensitivity and accuracy [30,31]. Acute malnutrition screening should not be reduced to mortality risk screening but also to prevent morbidity, impaired physical, cognitive development, and associated micronutrient deficiencies [32].…”
Section: Plos Onementioning
confidence: 99%
“…In the latest 2013 guideline for the management of severe acute malnutrition, the World Health Organization (WHO) recommends using Mid Upper Arm Circumference (MUAC) at community level to screen for SAM [4]. A recent meta-analysis published in 2018 [5] supports this recommendation that communities through different platforms could perform routine screenings of young children with MUAC and improve thereby detection of SAM cases. However, over the last years, several papers have highlighted that the current practice to identify children with acute malnutrition, at least in a non-emergency context, can be improved considerably by increasing the current WHO recommended cut-offs for MUAC [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The MUAC measurement was used over weight-for height below -3 SD of the WHO standards because both of these measures give almost similar prevalence of SAM [3]. MUAC is regarded as a cost-effective and easiest method to early detect SAM in children with minimal risk and many potential bene ts [34]. We found that only 5.…”
Section: Discussionmentioning
confidence: 97%